1993
DOI: 10.1056/nejm199302043280503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ranitidine and Amoxicillin plus Metronidazole on the Eradication of Helicobacter pylori and the Recurrence of Duodenal Ulcer

Abstract: In patients with recurrent duodenal ulcer, eradication of H. pylori by a regimen that does not have any direct action on the mucosa is followed by a marked reduction in the rate of recurrence, suggesting a causal role for H. pylori in recurrent duodenal ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
284
2
7

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 663 publications
(301 citation statements)
references
References 17 publications
8
284
2
7
Order By: Relevance
“…4, 8±10 Hentschel et al reported that the combination of amoxycillin, metronidazole and an H 2 -receptor antagonist was effective in the treatment of H. pylori infection. 11 We showed that the substitution of clarithromycin for metronidazole (amoxycillin±clari-thromycin±H 2 -receptor antagonist therapy) was also effective and, as expected, effectiveness was not reduced by metronidazole resistance. 12 Subsequent studies showed that a proton pump inhibitor could be substituted for the H 2 -receptor antagonist with good SUMMARY Background: Effective anti-Helicobacter pylori therapies with few side-effects are needed.…”
Section: Introductionsupporting
confidence: 63%
“…4, 8±10 Hentschel et al reported that the combination of amoxycillin, metronidazole and an H 2 -receptor antagonist was effective in the treatment of H. pylori infection. 11 We showed that the substitution of clarithromycin for metronidazole (amoxycillin±clari-thromycin±H 2 -receptor antagonist therapy) was also effective and, as expected, effectiveness was not reduced by metronidazole resistance. 12 Subsequent studies showed that a proton pump inhibitor could be substituted for the H 2 -receptor antagonist with good SUMMARY Background: Effective anti-Helicobacter pylori therapies with few side-effects are needed.…”
Section: Introductionsupporting
confidence: 63%
“…Helicobacter pylori as the cause of active chronic gastritis, this new gastric pathogen has been firmly established as the major etiological agent of peptic-ulcer disease, and it is now strongly linked to development of gastric adenocarcinoma and gastric lymphoma (9,13,18,19,24,26,37,40,42,43,52). Although gastric spiral organisms have been observed in dogs and cats for over 90 years, their presence in these species has been largely ignored and they were sometimes cited as gastric commensals (3,23,50).…”
Section: Since the Discovery In 1983 By Warren And Marshall Ofmentioning
confidence: 99%
“…It survives in the acidic environment of the gastric mucosa and causes gastritis, peptic ulcers, mucosa-associated lymphoid tissue lymphoma, and gastric cancer [2]. Therefore, the eradication of H. pylori can markedly lower gastric and duodenal ulcer recurrence and allowing the treatment of mucosa-associated lymphoid tissue lymphoma [3]. The first-line choice of treatment for H. pylori infection in the United States and Europe consists of a conventional triple therapy, in which a proton pump inhibitor (PPI), clarithromycin, and amoxicillin are administered for 7-14 days [4][5][6].…”
Section: Introductionmentioning
confidence: 99%